2004
DOI: 10.1007/bf03033745
|View full text |Cite
|
Sign up to set email alerts
|

Short term arterial remodelling in the aortae of cholesterol fed New Zealand white rabbits shown in vivo by high-resolution magnetic resonance imaging — implications for human pathology

Abstract: High-resolution, non-invasive imaging methods are required to monitor progression and regression of atherosclerotic plaques. We investigated the use of MRI to measure changes in plaque volume and vessel remodelling during progression and regression of atherosclerosis in New Zealand White rabbits. Atherosclerotic lesions were induced in the abdominal aorta by balloon injury and cholesterol feeding. MR images (2D) of the abdominal aorta were acquired with cardiac and respiratory gating using a fast spin echo seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Conventional imaging techniques such as angiography are optimized only to detect the focal and high-grade stenosis without the ability to identify vessel wall changes, since the arteries can compensate for the progressive growth of atherosclerotic plaques by increasing their external circumference, thereby maintaining lumen diameter [13]. Therefore, the radiological assessment of atherosclerosis needs to shift emphasis from the vascular lumen to the arterial wall.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Conventional imaging techniques such as angiography are optimized only to detect the focal and high-grade stenosis without the ability to identify vessel wall changes, since the arteries can compensate for the progressive growth of atherosclerotic plaques by increasing their external circumference, thereby maintaining lumen diameter [13]. Therefore, the radiological assessment of atherosclerosis needs to shift emphasis from the vascular lumen to the arterial wall.…”
Section: Discussionmentioning
confidence: 98%
“…MRI studies on atherosclerosis in various animal models, including rabbits [17], have been widely reported [20,21]. Atherosclerosis of the aorta is the most frequent model used for MRI investigations, and few studies were involved in carotid artery in rabbit models [13]. The reasons why we selected the RCCA of rabbits for our experiments are the following: (1) carotid artery atherosclerosis refers to one of the highest clinical prevalence of the disease; (2) anatomically common carotid artery of relatively large size is located in a superficial position with a straight course and insignificant motion, all of which make it highly suitable for MRI evaluation of the vessel wall using a surface coil or a cylindrical knee coil; (3) the symmetric presence of the contralateral left common carotid artery serves as a perfect intraindividual control artery for MRI comparative analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Using these techniques, mean aortic atheroma thickness has been shown to progressively increase after 12 weeks of high cholesterol diet, with regression at 6 months using statins and selective PPAR-gamma agonist agents [47,55]. This atheroma regression is associated with decreased macrophage number and MMP activity and increased SMC/collagen ratio, suggestive of plaque stabilisation [47].…”
Section: Endpoint Assessmentmentioning
confidence: 96%
“…Rabbits provide a convenient model in that the aortic lumen is a static structure of the order of 4-5 mm in diameter, well within the spatial limits of non-invasive MRI [55]. Using these techniques, mean aortic atheroma thickness has been shown to progressively increase after 12 weeks of high cholesterol diet, with regression at 6 months using statins and selective PPAR-gamma agonist agents [47,55].…”
Section: Endpoint Assessmentmentioning
confidence: 99%
“…Magnetic resonance imaging was repeated every 3 months and showed increasing wall volume during the high-cholesterol diet phase and decreasing wall volume during the normal diet phase, once again confirming the ability of MR to monitor disease. 7 In another experimental study, Corti et al 8 demonstrated the beneficial effects of statins on atherosclerotic burden measured by MRI and compared it with the additional antiatherogenic benefits of combining a peroxisome proliferator-activated receptorYF agonist with simvastatin. histology and reproducibility, makes it a promising modality for tracking of disease in response to drug treatment.…”
Section: Plaque Regression In Animal Studiesmentioning
confidence: 98%